Tablet Formulation with Galactomannan Binding Agent and Acute Toxicity Test from Terminalia catappa L. - Nilsya Febrika Zebua; Tandra Alexandro; Virda Widya Pratiwi; Syarifah Nadia; Supran Hidayat; Muflihah Fujiko; Muharni Saputri; Tedy Kurniawan Bakri; Nerdy (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Ketapang is one of the many medicinal plant species that grow in Indonesia and is used to treat various diseases. Ketapang leaves contain flavonoids, tannins, saponins, and terpenoids that have anti-inflammatory, antioxidant, antiviral, and antimicrobial properties. This study aimed to determine the LD50 and histopathology of Liver and kidney damage before the formulation of tablets containing galactomannan-binding agents. The toxicity determination method was carried out in vivo in experimental animals at doses of 4g/kg BW, 8g/kg BW and 16g/kg BW, and Liver and kidney histopathology was carried out before formulation into tablet preparations using the wet granulation method with various concentrations of binders and disintegrants, namely F1(8:0), F2(0:8), F3(4:4), F4(2:6), and F5(6:2). The results of the toxicity test showed an LD50 of 15.9959, liver damage at a dose of 4 g/kg BW hepatocyte karyorrhexis cells, central vein constriction, sinusoidal dilatation, a dose of 8 g/kg BW hepatocyte karyorrhexis, significant venous congestion, sinusoidal dilatation, a dose of 16 g/kg BW hepatocyte cells, karyolysis, dilated central veins, and dilated sinusoids. The results of the tablet mass preformulation test meet the requirements: the flow time test was 1.48-2.14 g/second, the angle of repose test was 24.60°-30.60°, and the tab index test was 5.33%-9.33%. The results of the tablet evaluation test were as follows: the tablet hardness test was 3.8-8.6 kg, the tablet friability test was 0.167-0.64%, and the tablet disintegration time test was 29.06-107.51 minutes.